INTERNATIONAL PERSPECTIVES ON A COLLECTIVE APPROACH TO RECOVERY AND CITIZENSHIP - Bromage, Billy; Maclean, Kirsten; Gobbo, Marcelo; Cheng, Winnie; Cáceres Malig, Denisse; Souza da Rocha, Nathália Maria; Willianmson, Bridgett; Rowe, Michael (Brazilian Journal of Mental Health, 2021)
In recent years, the citizenship framework has been refined and expanded by mental health practitioners from around the world who have applied it to their cultural and sociopolitical contexts. One driving factor in the process has been in-person cultural exchanges to observe how citizenship theory is operationalized in practice. Since 2015, Focus Act Connect Every-day (FACE) has welcomed visitors from South America, Asia and Europe to participate in its group meetings and community-building activities in New Haven, Connecticut, USA. FACE is a collective of people in recovery, mental health practitioners, and other community members that operates outside of the mental health service system and provides mutual support to its members and participates in community-building work in local neighborhoods. Using reflections on their experiences with FACE, the authors discuss how FACE and its unique application of the citizenship framework might pertain to their own contexts. Further, the authors consider the potential for promoting civic engagement and building community power that implementing projects similar to FACE might have, particularly among marginalized groups.